2014
DOI: 10.1016/j.bbr.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mononuclear cell transplantation promotes therapeutic angiogenesis via upregulation of the VEGF–VEGFR2 signaling pathway in a rat model of vascular dementia

Abstract: Bone marrow mononuclear cells (BMMNCs) are important for angiogenesis after stroke. We investigated the effects of BMMNCs on cognitive function, angiogenesis, and the vascular endothelial growth factor (VEGF)-VEGF receptor 2 (VEGFR2) signaling pathway in a rat model of vascular dementia. We transplanted BMMNCs into rats that had undergone permanent bilateral occlusion of the common carotid arteries (2VO) and observed their migration in vivo. On day 28, we assessed cognitive function with the Morris Water Maze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…We also examined the effect of MNCs on vessel density. Several studies have shown that MNCs provide protection in a model of chronic cerebral ischemia-induced cognitive dysfunction by increasing angiogenesis [50,51]. Others have demonstrated that MNCs increase vascular density and blood flow in various ischemic disorders such as cardiovascular disease, peripheral arterial disease, and diabetic foot [52].…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the effect of MNCs on vessel density. Several studies have shown that MNCs provide protection in a model of chronic cerebral ischemia-induced cognitive dysfunction by increasing angiogenesis [50,51]. Others have demonstrated that MNCs increase vascular density and blood flow in various ischemic disorders such as cardiovascular disease, peripheral arterial disease, and diabetic foot [52].…”
Section: Discussionmentioning
confidence: 99%
“…Sections were stained with Luxol fast blue (LFB) to evaluate the amount of myelin in the WM as previously described (Wang et al, 2014;Wu et al, 2012). Three sections per rat were obtained, and three randomly chosen fields from the middle of the corpus callosum and the corpus striatum of each section were captured under light microscopy at the same exposure level.…”
Section: Wm Damagementioning
confidence: 99%
“…However, the abrupt decrease in CBF during the acute phase after the 2VO procedure causes substantial mortality rates in rats (50-60%) (Wang et al, 2014;Shibata et al, 2004). Many modified 2VO protocols have been explored to minimize the number of animals used in research by alleviating the sudden reduction of CBF.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor receptor-2 (VEGFR-2) is a type III transmembrane receptor. VEGF binding to VEGFR-2 leads to the receptor autophosphorylation (activation), which initiates several downstream signalings [56, 57]. However, as the protein level of VEGF decreases 7 to 14 days following ICH, the p-VEGFR-2 signaling becomes weaker and weaker [58].…”
Section: Discussionmentioning
confidence: 99%